Economic Evaluation of Health Cost of Pesticide Use: Willingness to Pay Method (The Pakistan Development Review, 2009)
This study highlights the results of contingent valuation method to measure health cost of pesticide use from farmer’s point of view. Analysis shows that farmers have a positive willingness to pay for avoiding pesticide related health risks. Theoretical validity tests show that relevant indicators such as risk perception, previous experience of pesticide related poisoning, education and income are significant predictors for the positive WTP. From the results it is evident that health effects of pesticide use provided motivation for farmers to pay more for practices like IPM that reduce dependence on pesticide use which in turn a strong motivation for policy-makers to continue research on IPM and its implementation. Keywords: Health Cost, WTP, Pesticide Use, IPM.